Validation of an MRI‐based method to assess patellofemoral joint contact areas in loaded knee flexion in vivo. Issue 4 (4th September 2013) - McWalter, Emily J.; O'Kane, Colm M.; FitzPatrick, David P.; Wilson, David R.
Abstract : Purpose: To develop and validate short axial and sagittal MRI scans (<1min) to assess in vivo patellofemoral contact areas in loaded knee flexion. Materials and Methods: Contact area was assessed in four cadaver knee specimens from axial and sagittal scans using two contact area extraction techniques (delineation and intersection) and three calculation techniques (slice thickness multiplication, linear interpolation, and spline interpolation). Error was expressed as the mean absolute and percentage difference from a dye staining‐based reference standard. Intrareader and intrasubject repeatability, expressed as the mean standard deviation, was determined. Results: Contact area assessments from the sagittal MRI scans using the delineation and slice thickness multiplication technique had the smallest error (47.7 ± 38.1 mm 2 or 10.7%). The intrareader repeatability from assessments using the sagittal scans was smaller than those using the axial scans when the delineation method was used (<9.4 ± 4.3 mm 2 and <15.4 ± 14.1 mm 2, respectively). The intrasubject repeatability of the assessment from the sagittal scan was less than 39.9 ± 23.0 mm 2 . Conclusion: This protocol yields assessments of contact area in less than 1 minute that have errors similar to those made using scans many times longer and can be used in series with kinematic scans to carry out simultaneous assessments in vivo to study patellofemoral joint disease.J. Magn. Reson. Imaging 2014;39:978–987. ©2013 Wiley Periodicals, Inc .